ECG concerns doctor on the field: Case report - Vukoje Vesna; Itov Nikolaj (ABC: časopis urgentne medicine, 2015)
INTODUCTION: The electrocardiogram is a very important diagnostic tool, but with rhythm disturbances and branch blocks, due to lack of diagnostic methods in the field we have a lot of dilemmas. The aim is to present the case of a patient who had registered a very wide complex tachycardia, regular rhythm, resulting in the field of complete right bundle branch block. It was a dilemma whether to treat it as a broad complex tachycardia of or STEMI heart attack, although it can often occur together. CASE REPORT: We used a case report a patient who is clinically and had a history of myocardial infarction with the data that previously has complete right bundle branch block, but that he had no ECG. The new recorded a very wide complex tachycardia with a frequency of 140. There was a dilemma of how to treat the patient. Do you give him some antiarrhythmic and drive it to the reception or save it for thrombolysis and drive to the gym for catheterization. I asked myself a simple question that has helped me to solve the dilemma and make the right decision. The question was, how would it look Ekg patients who have a history of complete right bundle branch block, and subsequently develop a heart attack. I tried to imagine the image of right bundle branch block, the drain at the drain and to compare this image with the new changes. I brought the conclusion that it is inferoposterolateral infarction. Three cardiologists at the reception had three different interpretations of this ECG, or coronary angiography, which I prepared the patient confirmed my diagnosis. CONCLUSION: The field work carries its own specifics. We work in the same conditions, but not all of equal qualifications nor knowledge from the same area, but we all have to make the right decisions. In larger centers for the reception and there is a cardiologist and internist. We do not have the ability to come up with some of my fellow consult, but because we need to have a broad knowledge which should permanently improve.